Standardized Clinical Assessment And Management Plans (SCAMPs) Provide A Better Alternative To Clinical Practice Guidelines - Farias, Michael (2013)
Variability in medical practice in the United States leads to higher costs without achieving better patient outcomes. Clinical practice guidelines, which are intended to reduce variation and improve care, have several drawbacks that limit the extent of buy-in by clinicians. In contrast, standardized clinical assessment and management plans (SCAMPs) offer a clinician-designed approach to promoting care standardization that accommodates patients’ individual differences, respects providers’ clinical acumen, and keeps pace with the rapid growth of medical knowledge. Since early 2009 more than 12,000 patients have been enrolled in forty-nine SCAMPs in nine states and Washington, D.C. In one example, a SCAMP was credited with increasing clinicians’ rate of compliance with a recommended specialist referral for children from 19.6 percent to 75 percent. In another example, SCAMPs were associated with an 11–51 percent decrease in total medical expenses for six conditions when compared with a historical cohort. Innovative tools such as SCAMPs should be carefully examined by policy makers searching for methods to promote the delivery of high-quality, cost-effective care.